Pelatihan Daring Penggunaan Microsoft PowerPoint Tingkat Dasar bagi Aparatur Sipil Negara (ASN) dan Lembaga Kemasyarakatan Kelurahan (LKK) di Kelurahan Sukawarna - Kartika Suhada; Vivi Arisandhy; Rainisa Maini Heryanto; David Try Liputra; Santoso Santoso; Rudy Wawolumaja; Christophorus Ivander Menori; Grace Vania (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Kelurahan Sukawarna is one of the public facilities provided by the government to deliver service to the community within Kecamatan Sukajadi. To provide good service, one good way that can be done is to improve the knowledge and skills of ASN and LKK at Kelurahan Sukawarna. Currently, they use Microsoft PowerPoint, but some of them have only a low level of mastery, so the use of Microsoft PowerPoint in supporting their work is not optimal. Therefore, lecturers from the OSI expertise group and students carried out community service activities in training on the use of Basic Microsoft PowerPoint for ASN and LKK at Kelurahan Sukawarna. Considering the current Covid-19 pandemic, the training was conducted online using the Zoom Cloud Meetings application. The training was held for two days. On the first day, participants were given training material about using Microsoft PowerPoint, namely the File, Home, Insert, Design, Transitions, and Animations features. On the second day, training evaluation was carried out by giving assignments to the participants. Based on the assessment results of assignments, it can be seen that the participants made assignments well. The features taught in training had been used well in the assignments. The training benefits ASN and LKK at Kelurahan Sukawarna in improving their knowledge and skills in using Basic Microsoft PowerPoint. With this improvement, it is hoped that they can deliver better service to the community, e.g., socializing the prevention of Covid-19 and so on.